The anti-proliferation and pro-apoptosis of hydroxybenzoate calcium complexes in HT-1080 human fibrosarcoma cells - Mahdi, Jassem G.; Al-Musayeib, Nawal M.; Mahdi, Eamon J.; Abdulsatar, Asma J.; Pepper, Chris J. (European Journal of Oncology and Environmental Health, 2014)
Aim: Hydroxybenzoic acids are one of the major classes of phenolic compounds and are widely distributed in the phytochemicals of various plants. The aim of this study is to assess the efficacy of 2-, 3- and 4-hydroxybenzoate calcium (HBCa) complexes on HT-1080 cells and examine their anti-proliferative and pro-apoptotic effects in relation to 2-acetylbenzoic acid (2-ABA), or aspirin. Materials and Methods: The cytotoxicity of HBCa complexes was analysed in HT-1080 cells by MTT assay. Immunochemical and morphological assessment techniques were conducted to detect apoptosis, while Western blot was used to measure the expression of pro- and anti-apoptotic proteins. Results: The current in vitro study showed that HBCa complexes exert their cytotoxic activity in a concentration and chemical structure-dependent manner. 4-HBCa showed more potency than 3-HBCa, 2-ABA and 2-HBCa analogues. HBCa complexes inhibited cell proliferation, inducing apoptosis and cell cycle arrest at G0/G1 in human fibrosarcoma HT-1080. In addition, HBCa complexes modulated anti-apoptotic protein Bcl-2 and the induction of Bax, p53 and caspases-3 in favour of apoptosis. Conclusion: These results suggest that the apoptotic effects of the HBCa complexes are driven via the intrinsic apoptotic pathway which is regulated, at least to some extent, by the relative expression of Bcl-2 family proteins. The increased potency of 4-HBCa compared to 2-HBCa, 3-HBCa and 2-ABA provides a rationale for the continued exploration of these analogues as anti-cancer agents.